Electronic and optical properties of low-dimensional group-IV monochalcogenides - Gomes, Lídia C. [UNESP]; Carvalho, A. (AIP Publishing, 2020)
The group-IV monochalcogenides are a set of binary materials M X composed by a group-IV element (M = Sn or Ge) and a chalcogen (X = S or Se). Strong anisotropy is one of the most interesting facets of these materials, especially in their low-dimensional form. In this Tutorial, we present some of the recent studies on the electronic and optical properties of 2D group-IV monochalcogenides, including predictions from first-principles density functional theory calculations and available experimental observations. We discuss the variation of the bandgap from bulk down to monolayer and the respective band structures, which are characterized by multiple valence and conduction band valleys, making these materials suitable for a variety of applications, including valleytronics. We also discuss the emergence of spin-orbit splitting, piezoelectricity, and ferroelectricity as a result of the polar character of the monolayers. Current predictions of carrier mobilities in monolayers and their potential application as thermoelectric materials are also presented.